Penerapan Etika Dalam Penyelenggaraan Pelayanan Publik - Susanty, Yunni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
Implementation of ethics in public service has not run as expected. The systems weakness that supported by lack of quality and quantity of human resources act as inhibiting factor to achieve high performance in public services. In addition, moral and ethical violations that occurred generate some dilemma. There is high expectance to achieve professional and accountable public service, but on the other hand, moral and ethical issues are problems that are not easy to be addressed. For that matter, ethics must always be considered in every phase of public service. If every apparatus implement ethics in public service, then organization will achieve high performance. Therefore, ethics as one mportant element in public service must constantly be developed to meet public expectations.